3D Plant cell architecture of Arabidopsis thaliana (Brassicaceae) using focused ion beam–scanning electron microscopy1. (4th June 2014) - Bhawana,; Miller, Joyce L.; Cahoon, A. Bruce
Abstract : Premise of the study: Focused ion beam–scanning electron microscopy (FIB‐SEM) combines the ability to sequentially mill the sample surface and obtain SEM images that can be used to create 3D renderings with micron‐level resolution. We have applied FIB‐SEM to study Arabidopsis cell architecture. The goal was to determine the efficacy of this technique in plant tissue and cellular studies and to demonstrate its usefulness in studying cell and organelle architecture and distribution. Methods: Seed aleurone, leaf mesophyll, stem cortex, root cortex, and petal lamina from Arabidopsis were fixed and embedded for electron microscopy using protocols developed for animal tissues and modified for use with plant cells. Each sample was sectioned using the FIB and imaged with SEM. These serial images were assembled to produce 3D renderings of each cell type. Results: Organelles such as nuclei and chloroplasts were easily identifiable, and other structures such as endoplasmic reticula, lipid bodies, and starch grains were distinguishable in each tissue. Discussion: The application of FIB‐SEM produced 3D renderings of five plant cell types and offered unique views of their shapes and internal content. These results demonstrate the usefulness of FIB‐SEM for organelle distribution and cell architecture studies.